Densification effects on porous silica: A molecular dynamics study. (May 2018) - Tian, Ye; Du, Jincheng; Hu, Dongxia; Zheng, Wanguo; Han, Wei
Abstract: Molecular dynamics simulations are performed to investigate the effects of hydrostatic and shock densification on the structural and mechanical properties of porous silica. In the 0–35 GPa pressure range, the equation of state reveals a unique plastic-elastic transition for this material, resulting in a continuous density increase followed by saturation. Structural modifications are reflected in the medium-range order only, as evidenced by the increase of inter-tetrahedral bond angles occurring through the pressure-induced rearrangement of SiOSi planes and associated bonds. Discontinuous evolution of the elastic moduli for densified porous silica is observed and associated with the change of ring statistics. Graphical abstract: Unlabelled Image